Predictors of Severity in Autism Spectrum Disorders among Libyan Children: Cross-sectional analysis in Almarj - khalifa Mohamed, Munira; A. Betelmal, lbrahim (Libyan Journal of Public Health Practices, 2025)
Today, autism spectrum disorders (ASD) are among the most prevalent neurodevelopmental illnesses. Their varied degrees of severity influence and determine the necessary support and intervention. Risk elements of severity include the child's gender, parental age, and parental educational levels. In Libya, such factors are under-examined. This study aimed to identify predictors of autism severity in Libyan children diagnosed with ASD attending rehabilitation centers in Almarj. It adhered to ethical considerations by submitting a formal application to the centers and obtaining consent from participants. A cross-sectional study included 119 children diagnosed by the Childhood Autism Rating Scale(C.A.R.S) .Demographic information, including child gender, age, educational level, parental age, and education, was gathered through parent interviews. The 2 to 12 year-old sample comprised 73% males and 27% females, with a mean of 7.3 years. About 73.1% had their diagnosis after two years of age. The school achievement of the majority of them affected by Autism, as about 69% (N=82) were not at the appropriate school level for their age. Paternal age over 40 years was notably linked to affect autism severity (OR = 0.198, 95% CI: 0.059–0.661, p = 0.008). Child gender, maternal age, and parental education exhibited no significant connection. Although all registered children with ASD was included, the small sample size limit the ability to generalize the results. Early screening might help families with older fathers to get benefit from advantages of early Autism diagnosis in Libya. This study helps to optimize clinical management and improve regional outcomes for children with ASD